Greater benefit of self-affirmation for prevention-focused individuals prior to threatening health messages. Issue 6 (14th June 2021) - Ferrer, Rebecca A.; Cerully, Jennifer L.; Harris, Peter R.; Klein, William M. P.
Abstract: Objective: Individuals are often defensive toward health messages that suggest they are putting their health at risk because such messages threaten their self-competence and integrity. Although self-affirmation can facilitate prevention behaviors in response to health messages, effects are variable. We examined whether disease prevention focus might strengthen self-affirmation's effects in response to disease prevention messages, given that prevention-focused individuals are likeliest to be persuaded by those messages after self-affirmation attenuates defensiveness. Design: In Study 1, participants were self-affirmed before a message about sexually transmitted infections. In Studies 2 and 3, individuals were self-affirmed prior to a message about alcohol and cancer risk. Main Outcome Measures: Studies assessed intentions to use condoms, intentions to reduce alcohol, and willingness to drink alcohol in specific scenarios. Results: In Study 1, self-affirmation facilitated condom use intentions among those higher in prevention focus. In Studies 2 and 3, self-affirmation facilitated lower willingness to consume alcohol among those high in prevention focus. A meta-analysis across the three studies indicated that self-affirmation improved intentions and willingness under high, but not low, prevention focus ( d = 0.20, p = .003). Conclusion: These findings demonstrate that health prevention-focus can strengthen self-affirmation's effects, thereby improving responsiveness to health communications about behaviors that increase disease risk.